Imagery-37: a virtual lab for computer assisted education on digital image processing - Montenegro Joo, Javier (2008)
Imagery is a Virtual Lab for computer-assisted traning on Digital Image Processing(DIP), currently including 37 modules. Thhis software allows the user in the effects on real images; it may be used in the classroom, in the laboratory or at home. Imagery not only operates on images included by its creator(the author of this report), but also on those provided by the user. Some supporting theory is incluyed in Imagery, which may be used as a complement to specialized textbooks or classes.